Control of self-assembly in micro- and nano-scale systems. (March 2015) - Paulson, Joel A.; Mesbah, Ali; Zhu, Xiaoxiang; Molaro, Mark C.; Braatz, Richard D.
Abstract : Highlights: Describes challenges associated with the control of self-assembling systems. Describes the main strategies for addressing these challenges. Provides many specific examples to illustrate these strategies. Provides an outlook on future research directions for control of self-assembly. Abstract: Control of self-assembling systems at the micro- and nano-scale provides new opportunities for the engineering of novel materials in a bottom-up fashion. These systems have several challenges associated with control including high-dimensional and stochastic nonlinear dynamics, limited sensors for real-time measurements, limited actuation for control, and kinetic trapping of the system in undesirable configurations. Three main strategies for addressing these challenges are described, which include particle design (active self-assembly), open-loop control, and closed-loop (feedback) control. The strategies are illustrated using a variety of examples such as the design of patchy and Janus particles, the toggling of magnetic fields to induce the crystallization of paramagnetic colloids, and high-throughput crystallization of organic compounds in nanoliter droplets. An outlook of the future research directions and the necessary technological advancements for control of micro- and nano-scale self-assembly is provided.